Integration of Information and Communication Technology (ICT) to the Library and Information Science Curriculum: The Practicum in Library Schools in Rivers State - Alex-Nmecha, Juliet; Nsirim, Onyema (International Journal of Knowledge Content Development & Technology, 2023)
The study investigated the Integration of Information and Communication Technology (ICT) to the Library and Information Science Curriculum: The Practicum in Library Schools in Rivers State. Descriptive survey design was used with a population 374 comprising 21 LIS educators and 353 Four Hundred Level Library and Information Science Students from University of Port Harcourt, Rivers State University, Port Harcourt, and Ignatius Ajuru University of Education Port Harcourt. Census sampling technique was used to select the LIS educators and purposive sampling technique was used to the select the Four Hundred Level LIS students. Questionnaire and checklist were used for data collection. 90% and 97% responses were found valid for analysis for LIS Educators and LIS students respectively. The study was analyzed using mean rating, standard deviation and simple percentage. The study revealed that ICT courses were integrated into LIS curriculum in Library schools in Rivers State but LIS educators lacked the ICT skills to teach ICT practicum consequently, the students were not properly taught ICT practicum. However, students had positive perception of ICT practicum. Notwithstanding, lack of ICT skills, poor policy implementation, lack of state-of-the-art infrastructure and nonchalant attitudes of staff towards the adoption of ICT constituted the challenges faced in the implementation of ICT practicum. The study therefore, recommended that the management of library schools in Rivers State should implement ICT practicum by hiring competent staff maybe from computers science department to teach the practicum for the interim. Subsequently, recruitment of librarians should include strictly ICT compliant.